MODEL OPTIMALISASI CUSTOMER RELATIONSHIP MANAGEMENT DALAM MENINGKATKAN UNIT ENTRY - Avia, Muhammad Dusthin Putra; Raharja, Sam’un Jaja; Muftiadi, R. Anang (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This project aims to increase the number of unit entries at OtoXpert Karawang operated by Auto2000 through the optimization of the Customer Relationship Management (CRM) model. The method used in this project is applied research with a qualitative and quantitative approach. Data were collected through interviews, observations, and analysis of relevant documents. The project results show that the implementation of the optimized CRM model can increase the number of inquiries, boost the number of customers making bookings, and optimize the digital marketing process. Strategies such as the use of digital advertising (Meta Ads), optimization of social media content, and the implementation of Flow Charts and SOPs for booking conversion and post-service follow-up, have significantly increased the number of unit entries at OtoXpert Karawang. The conclusion of this project is that the optimization of the CRM model implemented at OtoXpert Karawang successfully enhances the performance of customer relations contributions to unit entry. Recommendations are provided to continuously improve and develop CRM strategies to achieve more optimal results in the future.